Pharmacokinetics and Bioequivalence of 2 Oral Formulations of Domperidone After Single‐Dose Administration in Healthy Chinese Subjects. Issue 9 (9th April 2022) - Ye, Libing; Shen, Minmin; Chen, Yingrong; Li, Xiaofeng; Xu, Min; Yao, Chong; Yang, Shuixin
Abstract: To evaluate the pharmacokinetic properties and bioequivalence of 2 oral formulations of domperidone in healthy Chinese subjects, a randomized, open‐label, 2‐way crossover study was conducted under fasting and fed states. All 96 healthy subjects were randomized to receive a single oral dose of a 10‐mg generic domperidone tablet (test) or branded domperidone tablet (reference). Blood samples were collected at specified time intervals and analyzed for domperidone using liquid chromatography–tandem mass spectrometry. In the fasting test, 90% CIs of geometric mean ratios were 86.7% to 105.8% for maximum concentration, 96.7% to 106.1% for area under the concentration‐time curve (AUC) from time 0 to the time of the last measurable plasma concentration, and 97.1% to 106.1% for AUC from time 0 extrapolated to infinity. In the fed test, the 90% CIs were 90.8% to 121.1%, 99.7% to 109.4%, and 99.4% to 109.1%, respectively. All 90% CIs were within the bioequivalence range of 80% to 125%, indicating that the 2 formulations were bioequivalent. In addition, the values of time to maximum concentration, terminal‐phase elimination half‐life, and AUC were significantly higher in the fed group than in the fasting group, suggesting that a high‐fat meal slowed down the absorption and elimination of domperidone and significantly increased domperidone exposure.